Search for the familon via B(+/-) --> pi+/-X(0), B(+/-) --> K(+/-)X(0), and B(0) --> K(0)(S)X(0) decays. - Ammar, R; Bean, A; Besson, D; Zhao, X; Anderson, S; Frolov, V; Kubota, Y; Lee, S; Poling, R; Smith, A; Stepaniak, C; Urheim, J; et al. (2001)
We have searched for the two-body decay of the B meson to a light pseudoscalar meson h = pi(+/-),K+/-,K(0)(S) and a massless neutral feebly interacting particle X(0) such as the familon, the Nambu-Goldstone boson associated with a spontaneously broken global family symmetry. We find no significant signal by analyzing a data sample containing 9.7x10(6) BBbar mesons collected with the CLEO detector at the Cornell Electron Storage Ring, and set 90% C.L. upper limits italicB(B(+/-) --> h(+/-)X(0)) = 4.9x10(-5) and italicB(B(0) --> K(0)(S)X(0)) = 5.3x10(-5). These limits correspond to a lower bound of approximately 10(8) GeV on the family symmetry breaking scale with vector coupling involving the third generation of quarks.